![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
a)\(\sqrt{4x}< =10\)
<=> 4x <= 100
<=> x <= 25
b) \(\sqrt{9x}>=3\)
<=> 9x >= 9
<=> x >= 1
c) \(\sqrt{4x^2+4x+1}=6\)
<=>\(\sqrt{\left(2x\right)^2+2\left(2x\right).1+1^2}=6\)
<=>\(\sqrt{\left(2x+1\right)^2}=6\)
<=>\(|2x+1|=6\)
<=>\(\orbr{\begin{cases}2x+1=6\\2x+1=-6\end{cases}}\)
<=>\(\orbr{\begin{cases}2x=5\\2x=-7\end{cases}}\)
<=>\(\orbr{\begin{cases}x=\frac{5}{2}\\x=\frac{-7}{2}\end{cases}}\)
d)\(\sqrt{9x-9}-2\sqrt{x-1}=6\)
<=>\(\sqrt{9\left(x-1\right)}-2\sqrt{x-1}=6\)
<=>\(3\sqrt{x-1}-2\sqrt{x-1}=6\)
<=>\(\sqrt{x-1}=6\)
<=> x - 1 = 36
<=> x = 37
f) \(\sqrt{2x+1}=\sqrt{x-1}\)
<=> 2x + 1 = x -1
<=> 2x - x = -1 -1
<=> x = -2
g)\(\sqrt{x^2-x-1}=\sqrt{x-1}\)
<=>x2 -x -1 = x -1
<=> x2 -x-x-1+1 = 0
<=> x2 - 2x + 0 = 0
<=> x(x-2) = 0
<=>\(\orbr{\begin{cases}x=0\\x-2=0\end{cases}}\)
<=>\(\orbr{\begin{cases}x=0\\x=2\end{cases}}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
Bài 1: Giải phương trình
a) ĐKXĐ: \(x\ge3\)
Ta có: \(\sqrt{100\cdot\left(x-3\right)}=\sqrt{20}\)
\(\Leftrightarrow\left|100\cdot\left(x-3\right)\right|=\left|20\right|\)
\(\Leftrightarrow100\cdot\left|x-3\right|=20\)
\(\Leftrightarrow\left|x-3\right|=\frac{1}{5}\)
\(\Leftrightarrow\left[{}\begin{matrix}x-3=\frac{1}{5}\\x-3=-\frac{1}{5}\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=\frac{16}{5}\left(nhận\right)\\x=\frac{14}{5}\left(loại\right)\end{matrix}\right.\)
Vậy: \(S=\left\{\frac{16}{5}\right\}\)
b) Ta có: \(\sqrt{\left(x-3\right)^2}=7\)
\(\Leftrightarrow\left|x-3\right|=7\)
\(\Leftrightarrow\left[{}\begin{matrix}x-3=7\\x-3=-7\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=10\\x=-4\end{matrix}\right.\)
Vậy: S={10;-4}
c) Ta có: \(\sqrt{4x^2+4x+1}=6\)
\(\Leftrightarrow\sqrt{\left(2x+1\right)^2}=6\)
\(\Leftrightarrow\left|2x+1\right|=6\)
\(\Leftrightarrow\left[{}\begin{matrix}2x+1=6\\2x+1=-6\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}2x=5\\2x=-7\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=\frac{5}{2}\\x=\frac{-7}{2}\end{matrix}\right.\)
Vậy: \(S=\left\{\frac{5}{2};\frac{-7}{2}\right\}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a, \(\sqrt{\left(\sqrt{2}\right)^2+2\times2\times\sqrt{2}+2^2}\)+ \(\sqrt{2^2+2\times2\times\sqrt{2}+\left(\sqrt{2}\right)^2}\)
= \(\sqrt{\left(\sqrt{2}+2\right)^2}\)+ \(\sqrt{\left(2-\sqrt{2}\right)^2}\)
= \(\sqrt{2}+2+2-\sqrt{2}\)
= 4
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\sqrt{4x^2}=6\Rightarrow\left|2x\right|=6\Rightarrow\left[{}\begin{matrix}2x=6\\2x=-6\end{matrix}\right.\) \(\Rightarrow x=\pm3\)
b/ ĐKXĐ: \(x\ge0\)
\(\sqrt{16x}=8\Leftrightarrow16x=64\Rightarrow x=4\)
c/ ĐKXĐ: \(x\ge1\)
\(\sqrt{9\left(x-1\right)}=21\Leftrightarrow\sqrt{x-1}=7\Leftrightarrow x-1=49\Rightarrow x=50\)
d/ \(\sqrt{4\left(1-x\right)^2}=6\Leftrightarrow2\left|1-x\right|=6\Leftrightarrow\left|1-x\right|=3\Rightarrow\left[{}\begin{matrix}x=-2\\x=4\end{matrix}\right.\)
e/ \(\sqrt{1-4x+4x^2}=5\Leftrightarrow\sqrt{\left(2x-1\right)^2}=5\Leftrightarrow\left[{}\begin{matrix}2x-1=5\\2x-1=-5\end{matrix}\right.\) \(\Rightarrow\left[{}\begin{matrix}x=3\\x=-2\end{matrix}\right.\)
f/ĐKXĐ: \(x\ge-\frac{1}{2}\)
\(\sqrt{9x^2}=2x+1\Leftrightarrow\left|3x\right|=2x+1\Leftrightarrow\left[{}\begin{matrix}3x=2x+1\\-3x=2x+1\end{matrix}\right.\) \(\Rightarrow\left[{}\begin{matrix}x=1\\x=-\frac{1}{5}\end{matrix}\right.\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a)...ghi lại đề...
\(\Leftrightarrow\sqrt{x^2-x-2x+2}=\sqrt{x-1}\)
\(\Leftrightarrow\sqrt{x\left(x-1\right)-2\left(x-1\right)}=\sqrt{x-1}\)
\(\Leftrightarrow\sqrt{\left(x-2\right)\left(x-1\right)}=\sqrt{x-1}\)
\(\Leftrightarrow\sqrt{x-2}\cdot\sqrt{x-1}=\sqrt{x-1}\)
\(\Leftrightarrow\sqrt{x-2}=\frac{\sqrt{x-1}}{\sqrt{x-1}}=1\)
\(\Leftrightarrow\sqrt{x-2}^2=1^2\)
\(\Leftrightarrow x-2=1\)(Vì \(x-2\ge0\Leftrightarrow x\ge2\))
\(\Leftrightarrow x=3\)
\(\)
\(a,\sqrt{x^2-3x+2}=\sqrt{x-1}\)
\(\Rightarrow x^2-3x+2=x-1\)
\(\Rightarrow x^2-4x+3=0\)
\(\Rightarrow x^2-x-3x+3=0\)
\(\Rightarrow\left(x-3\right)\left(x-1\right)=0\)
\(\Rightarrow\orbr{\begin{cases}x-3=0\\x-1=0\end{cases}\Rightarrow\orbr{\begin{cases}x=3\\x=1\end{cases}}}\)
Vậy..........
\(\sqrt{4x^2}=6\)
\(\left(\sqrt{4x^2}\right)^2=6^2\)
\(4x^2=36\)
\(x^2=9\)
\(x^2=\left(\pm3\right)^2\)
\(x=\pm3\)
\(\sqrt{4x^2}=6\)
\(\Leftrightarrow4x^2=36\)
\(\Leftrightarrow x^2=9\)
\(x=3\)